THE APPLICATION OF RISK BASED BANK RATING ON BANKRUPTCY PREDICTION OF BANKS IN INDONESIA - Evi Sistiyarini; Sudjarno Eko Supriyono (Jurnal Keuangan dan Perbankan, 2017)
The increase of banking products and services which is more complex will increase the risk to the banks. Therefore, to anticipate the rise of financial difficulties in a bank, the early warning system. This study aimed to find the influence RBBR (Risk Based Bank Rating) ratio’s to predict the bankruptcy of conventional Banks in Indonesia. The ratio of RBBR consisted of risk profile, Good Corporate Governance, profitability, and capital. Independent variables used were NPL, PDN, LDR, GCG, ROA and NIM, and CAR. The dependent variable was bank bankruptcy using a dummy variable. The population of this study was all of the conventional banks in Indonesia. The data was a secondary data taken form financial report of conventional bank 2011-2015. Technical sampling used was a purposive sampling method with some criteria. The analysis of this study used logistic regression. The result of the study showed that NPL, PDN, LDR, GCG, ROA and NIM, and CAR had no significant influence on the bankruptcy of the bank.